A Practical Synthesis of (S)-tert-Butyl 3-Methyl-1,4-diazepane-1-carboxylate, the Key Intermediate of Rho–Kinase Inhibitor K-115 - Gomi, Noriaki; Kouketsu, Akiyasu; Ohgiya, Tadaaki; Shibuya, Kimiyuki (Synthesis, 2012)
A practical synthesis of (S)-tert-butyl 3-methyl-1,4-diazepane-1-carboxylate has been established for supplying this key intermediate of Rho–kinase inhibitor K-115 in a multikilogram production. The chiral 1,4-diazepane was constructed by intramolecular Fukuyama–Mitsunobu cyclization of a N-nosyl diamino alcohol starting from the commercially available (S)- or (R)-2-aminopropan-1-ol. In the same manner, an enantiomeric pair of a structural isomer were prepared for demonstration of the synthetic utility.
Keywords: 1,4-diazepane; Fukuyama–Mitsunobu cyclization; cation-exchange resin; asymmetric molecule; Rho–kinase inhibitor